Parameter estimation using generating function based minimum power divergence measure / Tay Siew Ying - Tay, Siew Ying (2018)
This research proposes a parameter estimation method that minimizes a probability generating function (pgf) based power divergence with a tuning parameter to mitigate the impact of data contamination. Special cases arise when the tuning parameter approaches zero, resulting in a Kullback-Leibler type divergence, and when it takes on the value of one, resulting in a pgf-based